2013
DOI: 10.1507/endocrj.ej12-0455
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP11B2 polymorphisms with susceptibility to primary aldosteronism: a meta-analysis

Abstract: PRIMARY ALDOSTERONISM (PA) is characterized by overproduction of the mineralocorticoid hormone aldosterone by adrenal glands. According to recent reports, it appears to be the most common cause of secondary persistent hypertension, and may account for about 8~13% of unselected hypertensives [1] and as high as 20% of resistant hypertensives [2,3]. The inappropriately high production of aldosterone causes suppression of plasma renin, sodium retention, hypertension, cardiovascular damage, and potassium excretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, previous studies on the CYP11B2 T-344C polymorphism have shown a significant 21 , 39 or lack of association with hypertension and other cardiovascular parameters 40 . Moreover, Jia et al suggested that the -344C allele may be associated with a decreased risk of idiopathic hyperaldosteronism 41 . Further studies are warranted to elucidate the role of CYP11B2 C/C in the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous studies on the CYP11B2 T-344C polymorphism have shown a significant 21 , 39 or lack of association with hypertension and other cardiovascular parameters 40 . Moreover, Jia et al suggested that the -344C allele may be associated with a decreased risk of idiopathic hyperaldosteronism 41 . Further studies are warranted to elucidate the role of CYP11B2 C/C in the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Their study suggests that the -344C allele may be associated with a lower risk of developing idiopathic primary aldosteronism. 54 The association between transcription rate of CYP11B2 gene and its own polymorphism T-1651C was studied. Mc-Manus et al found that the transcriptional repressor − APEX1 binds the -1651T allele stronger than the -1651C allele, which results in reduced CYP11B2 expression and consequently lower aldosterone production.…”
Section: Mutations and Polymorphisms In Aldosterone Synthase Genementioning
confidence: 99%
“…The enzyme catalyzes the last step in the synthesis of the hormone aldosterone from deoxycorticosterone. Aldosterone, in turn, plays a role in the regulation of blood pressure by maintaining water-salt balance, is activated by potassium and promotes its excretion according to the principle of feedback (Gomes-Sanches et al, 2017;Jia et al, 2013;MdDonough et al, 2017).…”
mentioning
confidence: 99%